"Analytical, " "Angry, " and "(Too) Honest"?! Learners' Stereotypes about Teachers of German. Issue 2 (7th November 2022) - Rothe, Lucian
Abstract: This study investigated stereotypes about teachers of German that 67 novice learners of German at a U.S. university had reportedly encountered. Consequently, the investigation explored the perceived accuracy of clichés associated with native‐speaker and non‐native‐speaker instructors. Students' stereotypical notions were sorted into categories using principles of grounded theory. Statistical analyses showed that respondents were able to list various stereotypes about instructors of German. Responses also reflected societal narratives concerning native‐speaker and non‐native‐speaker teachers' strengths and shortcomings. Last, and of importance to the future of German Studies, participants considered more favorable stereotypes about teachers as more accurate and less‐favorable clichés as more inaccurate. The study discusses implications for teaching, program advertisement, and research on how learners' imagined construct of the language classroom community may benefit the study of German.